Life Cycle Assessment of Biochar from Residual Lignocellulosic Biomass Using Kon-Tiki Kilns: Applications in Soil Amendment and Wastewater Filtration - Roxanna Pamela Ramírez López; Diana Cabañas Vargas; Erick Alberto Aguilera-Cauich; Julio César Sacramento Rivero (Recycling, 2024)
Producing biochar from residual biomass is an opportunity for health, environmental, and economic benefits to farmers in small traditional parcels, which are widespread in Latin America. This study presents a life cycle assessment of biochar in two circular economy scenarios: soil amendment and wastewater filtration. Seven mid-point environmental impact categories were assessed using the CML-IA method: acidification (AP), abiotic depletion (ADP), fossil fuels depletion (ADP-FF), eutrophication (EP), global warming (GWP), human toxicity (HTP), and smog formation (POCP). The soil amendment scenario showed lower impacts per tonne of biochar in all categories, especially for GWP (−801.3 kg CO2eq) and ADP-FF (−374.3 MJ), compared to the filtration scenario (−123.54 kg CO2eq and 827.85 MJ). Negative GWP values reflect reduced emissions from avoided fertilizers and carbon sequestration. However, POCP and HTP increased due to air emissions (CH4, NOx, NMVOC, and PM10) from the kiln. In both scenarios, biochar production contributed to 40–90% of the total impacts. Indirect emissions from electricity used for water pumping were identified as a hotspot in the filtration scenario.